Abnormal pattern of left atrial activation and asynchronous conduction predicted the occurrence of new atrial fibrillation: evidences for Bachmann's bundle block in atrial fibrillation pathophysiology. Issue 8 (18th February 2021) - Seewöster, Timm; Marinov, Kaloyan; Löbe, Susanne; Knopp, Helge; Nedios, Sotirios; Bollmann, Andreas; Hindricks, Gerhard; Dinov, Borislav
Abstract: Aims: Evidences suggest that recurrent atrial fibrillation (AF) is associated with left atrial (LA) remodelling. The goal of this study is to establish a method for assessment of LA remodelling and find predictors for the development of AF. Methods and results: This prospective study included patients without a history of AF who were evaluated using pulsed-wave tissue Doppler imaging (PW-TDI). P-wave onset to A′-wave (PA′ interval) was measured at the septal, lateral, anterior, and inferior mitral annulus. Abnormal LA activation pattern was defined as an upward LA activation over the coronary sinus and delayed activation anterior. Left atrial asynchrony was measured as (i) the difference between the septal and lateral PA′ interval (DLS) and (ii) the standard deviation of all four PA′ intervals (SD4-PA′). The follow-up for AF recurrence (AF+) was based on symptoms and 7-day Holter electrocardiograms. Ninety-eight patients (mean age 58 ± 15 years, 47% female) were included. During a follow-up of 28 ± 9 months, AF was documented in 10%. More pronounced LA asynchrony was observed in AF+ group: DLS (AF+) 39 ± 16 vs. DLS (AF−) 20 ± 11 ms; P  < 0.001, and SD4-PA′ (AF+) 18.6 ± 6.4 vs. SD4-PA′ (AF−) 11.7 ± 4.2 ms; P  < 0.001. Abnormal LA activation was frequently observed in AF+ patients: 60% vs. 27%; P  = 0.033. Electrocardiogram sign of Bachmann's bundle block (BBB) was associated with prolongation of SD4-PA′: SD4-PA′ (BBB+) vs. SD4-PA′ (BBB−) = 18 ± 6 vs. 13 ± 4.5 ms; P  = 0.007. Conclusions: More pronounced LA asynchrony and abnormal LA activation pattern were associated with new-onset AF.